“Orphan” Connexin43 in Plakophilin-2 Deficient Hearts Revealed by Volume Electron Microscopy - van Opbergen, Chantal J. M.; Sall, Joseph; Petzold, Chris; Dancel-Manning, Kristen; Delmar, Mario; Liang, Feng-Xia (Frontiers in Cell and Developmental Biology, 2022)
Previous studies revealed an abundance of functional Connexin43 (Cx43) hemichannels consequent to loss of plakophilin-2 (PKP2) expression in adult murine hearts. The increased Cx43-mediated membrane permeability is likely responsible for excess entry of calcium into the cells, leading to an arrhythmogenic/cardiomyopathic phenotype. The latter has translational implications to the molecular mechanisms of inheritable arrhythmogenic right ventricular cardiomyopathy (ARVC). Despite functional evidence, visualization of these “orphan” (i.e., non-paired in a gap junction configuration) Cx43 hemichannels remains lacking. Immuno-electron microscopy (IEM) remains an extremely powerful tool to localize, with nanometric resolution, a protein within its native structural landscape. Yet, challenges for IEM are to preserve the antigenicity of the molecular target and to provide access for antibodies to reach their target, while maintaining the cellular/tissue ultrastructure. Fixation is important for maintaining cell structure, but strong fixation and vigorous dehydration (as it is routine for EM) can alter protein structure, thus impairing antigen-antibody binding. Here, we implemented a method to combine pre-embedding immunolabeling (pre-embedding) with serial block-face scanning electron microscopy (SBF-SEM). We utilized a murine model of cardiomyocyte-specific, Tamoxifen (TAM) activated knockout of PKP2. Adult hearts were harvested 14 days post-TAM, at this time hearts present a phenotype of concealed ARVC (i.e., an arrhythmogenic phenotype but no overt structural disease). Thick (200 µm) vibratome slices were immunolabelled for Cx43 and treated with nanogold or FluoroNanogold, coupled with a silver enhancement. Left or right ventricular free walls were dissected and three-dimensional (3D) localization of Cx43 in cardiac muscle was performed using SBF-SEM. Reconstructed images allowed us to visualize the entire length of gap junction plaques, seen as two parallel, closely packed strings of Cx43-immunoreactive beads at the intercalated disc. In contrast, in PKP2-deficient hearts we observed bulging of the intercellular space, and entire areas where only one of the two strings could be observed, indicating the presence of orphan Cx43. We conclude that pre-embedding and SBF-SEM allowed visualization of cardiac Cx43 plaques in their native environment, providing for the first time a visual complement of functional data indicating the presence of orphan Cx43 hemichannels resulting from loss of desmosomal integrity in the heart.